Finite Element Analysis of Automobile Axle Housing based on Internet-driven Collaborative Design Theory - Zhu Jianliu (Jixie chuandong)
In order to solve the problems of traditional automobile axle housing design and analysis of wide object space distribution,difficult collaborative design and poor interaction performance,a multiple analytic encoded method based on discrete wavelet transform algorithm to the compress axle housing data is used,and then a shared network drive collaborative hybrid system architecture to share and protect the axle housing analyze compressed data is created,a finite element analysis system of network drive cooperative automobile axle housing is combined with JSP.Servlet technology with secondary development of finite element and the numerical computing systems is built.Taking the Dongfeng hercules series axle dump truck as the research object,the model strength,deformation and life characteristics are studied.The results show that the finite element method and technical route based on network collaborative design theory has certain feasibility,which can overcome wide distribution,difficult collaborative design and interaction and poor performance,and the product into production efficiency can be improved and the production cost can be reduced.